95.4k views
3 votes
Precalculus question, image attached.

Precalculus question, image attached.-example-1
User Haoyuan Ge
by
5.6k points

1 Answer

5 votes

Answer:

g(x)= x+1

Explanation:


h(x)= (fog)(x)= f(g(x))

Given
f(x)= \sqrt[3]{x+2},
f(x)= \sqrt[3]{x+3}


f(g(x))= \sqrt[3]{x+3}


f(x)= \sqrt[3]{x+2}

Replace x with g(x)


f(g(x))= \sqrt[3]{g(x)+2}

Now we need to find out what we plug in for g(X) to get x+3 under the radical

g(x) +2 is under the radical. we need x+3 , so we replace g(x) with x+`

So g(x)+2 becomes x+1+2 is x+3

Hence g(x) is x+1


User Joe McMahon
by
5.0k points